PELAKSANAAN SULH DI JABATAN KEHAKIMAN SYARIAH SELANGOR DARUL EHSAN (JAKESS): SATU SOROTAN AWAL - Azahari, Raihanah (Jurnal Syariah, 2019)
The Selangor Syariah Court has gazetted the rules [2001 Syariah Court Civil Procedure (Sulh)] relating to sulh and has appointed legal officers to observe the sulh process. With the setting up of the rules, it is hoped that the family cases will be conducted without the need for lengthy trials. With supported by the statistic of successful cases which haved benefited from the process, this article is trying to analyses the implementation of sulh at the Selangor Syariah Court. The study shows that the rules has reduce the backlog of cases in the syariah court and lessen the stress and tension which usually occur in family cases. This article will also establish the primacy of sulh which had been a previously neglected aspect of Islamic doctrine and legal system. More importantly, this discussion will contibute towards constructing a conflict and dispute management system which adresses the needs and expectations of Muslim societies today.